THE SENTIMENT ANALYSIS OF INDONESIAN NATIONAL LIBRARY’S TWITTER AND INSTAGRAM - Cecep Ibrahim (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2021)
Social media is one of the technological devices that can be used by the public to disseminate data or information in real time. In this case, the approach used is the Social Media Analytic (SMA) framework, especially Sentiment Analysis (SA) using Brand24. Sentiment Analysis is a measurement of human sentiment/emotional on social media based on content analysis (positive/negative/neutral). This study aims to determine the analysis of sentiment on the twitter and instagram accounts of the national library. The research data was taken from Twitter and Instagram data analysis using the keywords @perpusnas1 #perpusnas #perpustakaannasional. The results showed that there were 24 mentions from twitter users and 55 mentions from Instagram users. On Twitter the number of positive sentiment analysis is 3, negative 3 and neutral is 18, while on Instagram the number of sentiment analysis is positive 33, negative 4, and neutral 18.